Internalisasi Nilai Ekoteologi Berbasis Kokurikuler dalam Membentuk Eco-civic Culture Siswa Madrasah Aliyah - Agus Dwi Santosa; Ratna Saidah; Ahmad Fahroni (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2026)
Environmental education in Madrasah Aliyah often emphasizes ecological knowledge while paying limited attention to integrating Islamic theological values to strengthen students' environmental awareness and responsibility. This study aims to explain how ecotheological values are internalized through co-curricular activities in shaping students' eco-civic culture within the context of an Islamic senior high school. This research employed a qualitative case study at MAN 2 Kota Kediri, Indonesia. Data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, teachers, co-curricular coordinators, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while trustworthiness was ensured through source, method, and time triangulation. The findings reveal three interrelated processes: (1) the internalization of ecotheological values establishes students' ecological awareness by integrating the Islamic concepts of khalifah, amanah, mizan, and islah into school culture; (2) eco-civic culture is fostered through students' active participation and collective responsibility in environmental activities; and (3) habituation and exemplary practices reinforce the transformation of ecotheological values into sustainable ecological behavior. These findings enrich the discourse on Islamic environmental education by demonstrating how religious values, co-curricular practices, and school culture collectively nurture students' ecological citizenship.